Рецензія на монографію:Eugeniu Coșeriu, Vocația universalității,Кишинів, 2021,484 с. - Кібак, Діана Вікторівна (Видавництво БДМУ, 2021)
Eugenio Coșeriu’s Monumental Centenary Event - 100 years since his birth, is successufully celebrated both in the space of his native lands and abroad. A series of scientific and cultural events are organized. In this context, Știința Publishing House launches the Eugeniu Coșeriu – Vocația universalității / Vocation of Universality book collection under the coordination of Gheorghe Popa. The book covers the protagonist’life in thematic section: in the field of linguistics, literature, interviews - dialogues with and about Eugenio Coseriu, evocations - confessions and reconstructions, reflections on the great coserian model, and, of course, at the end, the iconographic compartment that makes accessible the life in images of master Coseriu.
Review of monograph:Eugeniu Cosheriu,the vocation of universality,Kishiniv, 2021,484 p.
Keywords: Eugenio Coseriu, centenary, linguist, scientist, universality, book-review